Diagnostic accuracy of non-invasive tests for advanced fibrosis in patients with NAFLD: an individual patient data meta-analysis - Mózes, FE; Lee, JA; Selvaraj, EA; Jayaswal, ANA; Trauner, M; Boursier, J; Fournier, C; Staufer, K; Stauber, RE; Bugianesi, E; Younes, R; Gaia, S; et al. (BMJ Publishing Group, 2021)
Objective Liver biopsy is still needed for fibrosis staging in many patients with non-alcoholic fatty liver disease. The aims of this study were to evaluate the individual diagnostic performance of liver stiffness measurement by vibration controlled transient elastography (LSM-VCTE), Fibrosis-4 Index (FIB-4) and NAFLD (non-alcoholic fatty liver disease) Fibrosis Score (NFS) and to derive diagnostic strategies that could reduce the need for liver biopsies.